THE INFLUENCE OF THE PROBLEM BASED LEARNING MODEL ACCOMPANIED BY MULTIREPRESENTATION BASED PHYSICS STUDENTS WORKSHEETS ON JUNIOR HIGH SCHOOL STUDENTS' LEARNING MOTIVATION - Arifin, Ahmad Zainul; Mahardika, I Ketut; Budiarso, Aris Singgih (Universitas Negeri Padang, 2024)
This research examines the significant influence of using the problem-based learning model accompanied by multi-representation-based physics students worksheets on junior high school students' learning motivation. The study used a quasi-experiment with a nonequivalent control group research design. The research subjects were students in class VIII of SMP Katolik Santo Petrus Jember, even during the semester of the 2022/2023 academic year in May, with the number of respondents being 52 students divided into experimental and control classes. Data collection uses test techniques in the form of pretest-posttest and non-test in the form of questionnaire sheets accompanied by data analysis techniques in the form of normality test, independent sample t-test, and a right-tailed t-test. The research results show that the use of the problem-based learning model accompanied by multi-representation-based physics students worksheets has a significant influence on increasing junior high school students' learning motivation.